Evaluation of the Completeness of Inpatient Medical Records Based on the Strengths, Weaknesses, Opportunities, Threats (SWOT) Method at Welas Asih General Hospital - Elsa Fitriah; Intan Pujilestari; Matoeari Soelistijaningroem (CV. AFDIFAL MAJU BERKAH, 2025)
Incomplete medical documentation at hospitals poses a significant risk to patient safety and service quality. This study aimed to evaluate the completeness of inpatient medical records at Welas Asih General Hospital using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to formulate strategic recommendations. Employing a qualitative descriptive method, the research focused on inpatient medical records and key personnel, including medical record officers and clinical staff. Data were collected through observation, documentation review, and interviews, and analyzed by grouping findings into the four SWOT categories. Results revealed that the overall completeness rate was 64%, with critical forms such as surgical informed consent and Attending Physician forms showing particularly low rates (41% and 42%, respectively). The analysis identified key challenges, including a hybrid documentation system, low digital literacy, and high staff workload. In conclusion, the hospital's medical record completeness is suboptimal due to internal weaknesses and external threats, despite its existing strengths and opportunities. The findings underscore the urgent need for a systematic improvement plan focusing on structured digitalization and continuous staff training to enhance accountability and quality of care.